Biotic Response to Rapid Environmental Changes During the Permian–Triassic Mass Extinction - Guoshan Li; Guoshan Li; Guoshan Li; Yongbiao Wang; Sheng Li; Sheng Li; Tan Wang; Wei Liao; Baozhu Deng; Zhongping Lai (Frontiers in Marine Science, 2022)
The divergent patterns of Permian–Triassic mass extinction (PTME) have been extensively documented in varying water depth settings. We here investigated fossil assemblages and sedimentary microfacies on high-resolution samples from two adjacent sections of the South China Block: Chongyang from shallow-water platform and Chibi from deeper-water slop. At Chongyang, abundant benthos (over 80%), including rugose corals, fusulinids, calcareous algae, and large foraminifers, disappeared precipitously at the topmost of Changxing Formation grainstone, which suggested complete damage of the benthic ecosystem, confirming a sudden single-pulse extinction pattern. The end-Permian regression, marked by a karst surface, provided a plausible explanation for this extinction pattern. Whereas for the fauna in Chibi, the benthos was relatively abundant (20%–55%) with more trace fossils and lacking calcareous algae. Benthic abundance in Chibi reduced by two steps at the two claystone beds (Beds 10 and 18): bioclastic content dropped from an average of 50% in Beds 1–9 to 10% in Beds 11–17 and then to less than 5% in Beds 19–23, suggesting a two-pulse extinction. At the first pulse, large foraminifers were prominent victims in both shallow- and deeper-water settings. A plausible survival strategy for small-sized foraminifers was to migrate to deeper water to avoid extreme heat in shallow water. The early Triassic transgression prompted some small foraminifers to migrate back to original platforms and flourish briefly as disaster forms. At the Early Triassic mudstone with bottom-water settings in Chibi, the appearance of abundant small pyrite framboids (diameters of 4.74–5.96 μm), an indicator of intensified oxygen deficiency, was simultaneous with the two-step reduction of benthic diversity and abundance. Thus, anoxic conditions might be the main cause of the PTME at deeper-water settings. Our study is an example of the wider debate about biotic response to rapid environmental change for both the Permian–Triassic transition and modern days.